Needs Analysis of ‘English for Accounting’ in Tertiary Education - Wulan Rahmatunisa; Vina Agustiana (ELT in Focus, 2018)
This study focused on needs analysis and course design of English for accounting in tertiary education in Kuningan, West Java. It aimed to investigate the required learning materials and the suitable learning activities for accounting students of tertiary education. This study employed qualitative method. It was conducted in qualitative design with some data collected quantitatively through questionnaire and some collected qualitatively through interviews and document analysis from students and lecturers. The questionnaire was used for descriptive statistics, whereas interviews and document analysis were used for the collection of more in-depth and emergent data. This study revealed that listening and speaking skills are the priority in teaching English which is closely followed by writing and reading. The highest students’ preferences for classroom learning activities are vocabulary exercising, followed by simulation and grammar exercising. It is also found that most students consider English is important in their future career and they might need English to communicate with colleague and customer. This information target situation should be taken into consideration as the basis of syllabus and material development. The information from target situation analysis is important in ESP course since it is all about eliciting what the learners have to know related to their future career.